Do institutional investors prefer to invest in socially responsible companies? An empirical analysis in Turkey - (:unkn) unknown (Springer-Verlag Berlin Heidelberg, 2014)
Corporate social responsibility (CSR) has become an indispensible item on companies' agendas and even though the business discipline has been with us for a few decades, it started to attract much more attention recently. Companies are emphasizing the importance of addressing issues relating to the social, economic and environmental aspects of their operations which affect their stakeholders in addition to their core business activities. Actions undertaken by socially responsible companies may be considered as determinants in the decision making process of investors. This is especially the case with institutional investors, who have long term investment horizon and are more willing to invest in companies that are serious about CSR activities. Numerous analyses have been conducted in the literature regarding the relationship between institutional shareholding and corporate social performance mainly in developed countries. However, this study focuses on an emerging country-Turkey, and probes whether institutional investors have a tendency to invest in socially responsible companies utilizing logistic regression analysis. The empirical part of the study employs available dataset combining data relating to percentage of shares that are held by institutional investors with the financials and selected CSR measures for companies listed in Istanbul Stock Exchange. © 2014 Springer-Verlag Berlin Heidelberg. All rights are reserved.